Embracing Ingenuity in Dealing with Resource Constraints: A Case of UUM (S/O 13891) - Wan Ahmad, Wan Norhayati; Ali, Azharudin; Shafie, Rohami (UUM, 2021)
Malaysia’s higher education blueprint 2015-2025 has set out five aspirations to improve access, quality, equity, unity and efficiency of country higher education system. Its aims to create a higher education system that can sustainabily compete globally and ranks among the world’s leading education systems. Due to massive budget cuts for Malaysia’s higher education sector since 2016, Malaysian public universities have faced with great challanges between realizing high performance target and limited financial resources, and between delivering quality education and operating within a considerably tighter budget. This study explores how Malaysian public universities was impacted by the cut and how they manage and deal with the cuts. The study examines their ability to thrive or maintain a better performance through ingenious solutions and approaches, such as be innovative, creative and effective problem solver. Using a qualitative research methods, a case study have been carried out at University Utara Malaysia (UUM) to collect the research data. Methods used included interviews, survey, documents and content analysis. The participants included the vice chanselor, top management, deans, head of departments and academics. The results of the study showed interesting themes and findings regarding scarce resources, ingenious solutions and performance. It reveals how during the challenging pressure and constrain situation, institution and its members manage to create ingenious practices and practical solutions in order to sustain and improve performance. Implications for this study provide one example of what, why and how a higher education institution such as UUM practicing ingenious solutions via a new revenue streams (income generation), assets monetarization, cost, reduction, innovation and technology advancement, and strategic and value-added partnership. In a nuttshell, this study proposes the themes of ingenious practices that are necessary to be practiced and implemented accross public universities, as well as to other public and private sectors.